2021
DOI: 10.1128/msphere.00216-21
|View full text |Cite
|
Sign up to set email alerts
|

Ehrlichia chaffeensis TRP120 Is a Wnt Ligand Mimetic That Interacts with Wnt Receptors and Contains a Novel Repetitive Short Linear Motif That Activates Wnt Signaling

Abstract: Upon infecting mammalian hosts, Ehrlichia chaffeensis establishes a replicative niche in microbe-eating immune system cells where it expertly orchestrates infection and spread. One of the ways Ehrlichia survives within these phagocytes is by activating evolutionarily conserved signaling pathways including the Wnt pathway; however, the molecular details of pathway hijacking have not been defined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
97
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(100 citation statements)
references
References 88 publications
(143 reference statements)
3
97
0
Order By: Relevance
“…TRP120 contains a tandem repeat domain (TRD) centered between the N- and C- terminal domains. Various functional SLiMs have been reported within the N terminus, TRD, and C terminus that are relevant to E. chaffeensis infection, including posttranslational modification motifs, DNA-binding motifs, and ubiquitin ligase catalytic motifs (7). We previously reported that TRP120 stimulation results in transcriptional upregulation of GLI-1 in THP-1 cells (4).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…TRP120 contains a tandem repeat domain (TRD) centered between the N- and C- terminal domains. Various functional SLiMs have been reported within the N terminus, TRD, and C terminus that are relevant to E. chaffeensis infection, including posttranslational modification motifs, DNA-binding motifs, and ubiquitin ligase catalytic motifs (7). We previously reported that TRP120 stimulation results in transcriptional upregulation of GLI-1 in THP-1 cells (4).…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that TRP120 stimulation results in transcriptional upregulation of GLI-1 in THP-1 cells (4). Moreover, during E. chaffeensis infection Wnt and Notch signaling pathways are activated through ligand mimicry via TRP120 Wnt and Notch SLiMs (4, 7, 9, 10). Since GLI-1 is a major transcriptional factor of the Hh- signaling pathway and often cross-talks with Wnt and Notch signaling (35, 36), we investigated the possibility of Hh pathway activation during E. chaffeensis infection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…TRP120 interacts with Wnt and Notch receptors to activate both pathways, regulating apoptosis and autophagy and promoting bacterial survival. Furthermore, TRP120 stability and interaction with Wnt FZD receptors stimulate bacterial internalization and the infection of host cells [95,96]. This effector also modulates the expression of several genes and, therefore, regulates multiple processes, including cytoskeleton organization and apoptosis [93].…”
Section: Ehrlichia Chaffeensismentioning
confidence: 99%